Correction: Inference of past demography, dormancy and self-fertilization rates from whole genome sequence data. - Thibaut Paul Patrick Sellinger; Diala Abu Awad; Markus Moest; Aurélien Tellier (PLoS Genetics, 2021)
[This corrects the article DOI: 10.1371/journal.pgen.1008698.].